NEW NOTES (NOT BY OWN HAND) TO THE “INTERPRETING A WORD” - HAYRAPETYAN, VARDAN (Bulletin of Yerevan University H: Russian Philology, 2020)
The publication includes recent years’ additions to the author's book “Interpreting a Word: An Attempt of hermeneutics in Russian” published in the second edition in 2011. Questions of the theory and technique of interpretation, relations between natural sciences and humanities, literature and folklore, are considered, and a detailed plan of an unwritten book on general philology is presented. Various aspects of the writings of Pushkin, Dostoevsky, Tyutchev, Mandelshtam, and others are touched upon.
Keywords: hermeneutics, philology, folklore, natural and human sciences, metaphor, mirror, Pushkin, Dostoevsky, Tyutchev, Mandelshtam